2019
DOI: 10.1038/s41598-019-41361-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Urinary Proteome in a Patient-Derived Xenograft (PDX) Nude Mouse Model of Colorectal Tumor

Abstract: In this report, the urinary proteome from a patient-derived xenograft (PDX) model was examined at the peptide level to study the origins of urinary proteins in tumor-bearing nude mice. Urine was collected from PDX mice before and after colorectal tumor implantation. A total of 4,318 unique peptides were identified, and 78 unambiguous human-origin peptides were discerned in the PDX model urine. Unlike the differential urinary protein composition of tumor-bearing immunocompetent rat models, the differential urin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…All animal experiments were performed under sterile conditions at Percans Oncology Inc. specific-pathogen free facility and carried out in accordance with the National Institutes of Health guide for the care and use of laboratory animals. The procedure of PDX model establishment was referred to previous reports [14 , 26] . Briefly, 6–8 week-old female NOD/SCID mice (Beijing HFK Bio-Technology Co., LTD, Beijing, China) were used for the studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All animal experiments were performed under sterile conditions at Percans Oncology Inc. specific-pathogen free facility and carried out in accordance with the National Institutes of Health guide for the care and use of laboratory animals. The procedure of PDX model establishment was referred to previous reports [14 , 26] . Briefly, 6–8 week-old female NOD/SCID mice (Beijing HFK Bio-Technology Co., LTD, Beijing, China) were used for the studies.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the establishment of tumor cell lines is hindered by the low rate of success (1–10%, depending on the tissue of origin and state of disease progression). Patient-derived xenograft (PDX) [13] , [14] , [15] and tumor organoids [16] , [17] , [18] have been considered more clinically relevant models for original patient tumors. Yet the use of such systems still facing hurdles such as high cost, long duration and technical difficulties, etc.…”
Section: Introductionmentioning
confidence: 99%
“…An ~25-kDa band was detected only in wild-type females, as shown in Fig. 2C , but proteins of this band seem unlikely to be MUPs because the 25 kDa band is not always detected (data not shown), as shown in the study of Liu et al [ 21 ]; moreover, bands have also been detected in some MUP-KO mice (data not shown). Although we did not identify the ~25-kDa proteins in the present study, lipocalin 2 [ 22 ] is one possible candidate.…”
Section: Discussionmentioning
confidence: 65%
“…Chemosensitivity in cell culture alone often cannot recreate microenvironments or tumor heterogeneity in tumor tissues, so the results are often not accurate. At present, the model of "human tumor tissue xenotransplantation (PDX)" is the most recognized in the world (5)(6)(7). In this model, a small piece of tumor tissue taken from the patient is implanted into an experimental mouse to simulate its original growth environment, thus preserving the characteristics of the patient and the tumor to the maximum extent.…”
Section: Introductionmentioning
confidence: 99%